Effect of carbon sources for enhanced biological phosphate removal (EBPR) under tropical climate - Poh, Ann Choon Yan (2017)
The performance of the enhanced biological phosphorus removal (EBPR) process is greatly influenced by the polyphosphate accumulating organisms (PAOs) and glycogen accumulating organisms’ (GAOs) competition for carbon in the reactor. Several studies have established the relationship between temperature and carbon source with the EBPR efficiency. Higher temperature tends to have a lower phosphorus removal efficiency, but there are new studies which proved otherwise. New studies have shown that stable EBPR performance can be achieved at higher temperatures with the use of certain carbon source. Carbon source can be used to enrich PAOs and/or GAOs. Propionate is said to be a more favorable volatile fatty acids (VFA) for the EBPR process as it enriches PAOs instead of GAOs. Propionate-fed EBPR systems also showed a more stable and better phosphate removal efficiency. Therefore, this study will compare the effects of acetate-fed and propionate-fed EBPR biomass on the EBPR performance. Batch experiments using single carbon sources such as acetate, propionate and butyrate, which can be found in wastewater, and iso-butyrate will be used to investigate the effects of the different biomass on the VFA uptake rates; phosphate release and uptake; and the accumulation and degradation of glycogen and PHA components such as PHB, PHV, PH2MV. Batch experiments will be conducted at 25°C and 30°C to mimic the conditions of the tropical climate. From this study, it can be observed that propionate was the most favorable carbon source for both acetate-fed and propionate-fed biomass at 25°C and 30°C. In addition, propionate-fed biomass tends to have a better phosphorus uptake than acetate-fed biomass. Generally, batch experiments have a better EBPR performance at 30°C.